daf-16/FOXO and glod-4/glyoxalase-1 are required for the life-prolonging effect of human insulin under high glucose conditions in Caenorhabditis elegans - Mendler, Michael; Ibrahim, Youssef; Kukudov, Georgi; Fleming, Thomas; Bierhaus, Angelika; Riedinger, Christin; Schwenger, Vedat; Herzig, Stephan; Hecker, Markus; Tyedmers, Jens; Nawroth, Peter Paul; Morcos, Michael (Diabetologia, 2015)
The aim of this study was to determine the protective effects of human insulin and its analogues, B28Asp human insulin (insulin aspart) and B29Lys(ε-tetradecanoyl),desB30 human insulin (insulin detemir), against glucose-induced lifespan reduction and neuronal damage in the model organism Caenorhabditis elegans and to elucidate the underlying mechanisms.
Published online: 17 October 2014
Gesehen am 12.06.2020